Parents Behind Bars Children Beyond Books: Impact of Parental Incarceration on Education of Children - Ms. Saloni Rathore; Ms. Anu Singh; Ms. Alpika Verma; Mr. Prakhar Saxena; Mrs. Megha Mishra; Mr. Moiz; Prof. (Dr) Shaukat Ali (Educational Administration: Theory and Practice, 2024)
Children of incarcerated parents are one of the neglected sections of the society. Parental incarceration may substantially disrupt a child’s upbringing which may lead to numerous problems including their pursuit of education. This paper will examine how parental imprisonment affects the education of children in India. Although this topic has been slightly touched in India, studies from other nations show that children having incarcerated parents are exposed directly to the challenges of life, specifically with schooling, such as decreased participation in school, poorer grades, and higher rates of dropping out. Moreover, such children are also subjected to the indirect consequences of parental incarceration, such as weakened family dynamics and extra responsibilities which have a negative impact on their scholastic chances. This paper will identify and analyse the difficulties that children with imprisoned parents are likely to encounter and analyse the present legal framework in India directed towards the protection of educational rights of children of incarcerated parents. Further, this paper proposes and suggest inputs for policy reforms with regards to education and measures to protect children with incarcerated parents.